Characteristics of Oil in Water (o/w) Type Lotions Incorporated with Kappa/Iota Carrageenan. Issue 1 (March 2021) - Fransiska, D; Darmawan, M; Sinurat, E; Sedayu, B B; Wardhana, Y W; Herdiana, Y; Setiana, G P
Abstract: Increasing public demand for cosmetics, especially those derived from natural materials, has provided seaweed opportunities as raw material for cosmetics. Kappa and iota carrageenans produced from red seaweed (Rhodophyceae) be used as a thickener and stabilizer in lotion formulations. This study aimed to determine the characteristics of lotion oil/water (o/w) type using kappa and iota carrageenan in the formulations. The research started with the optimization of lotion formulas. Four formulas obtained were 0% carrageenan (without carrageenan), 0.2% of kappa-carrageenan, 0.2% of iota-carrageenan, and a mixture of 0.2% kappa-carrageenan and 0.1% iota-carrageenan (2:1). Parameters observed were the organoleptic test, pH, viscosity, spreadability, microbial contamination, and a hedonic test. The results showed that kappa and iota carrageenan could be used to formulate lotion o/w type with a concentration of ⩽0.2%. The best formulation that meets the Indonesian National Standard (SNI) based on physical evaluation and hedonic test (parameters of moisture and sticky feeling) was the lotion formula with 0.2% of iota carrageenan.